Protection from experimental cerebral malaria with a single intravenous or subcutaneous whole-parasite immunization - Kirsten Heiss; Marion Irmgard Maier; Angelika Hoffmann; Roland Frank; Martin Bendszus; Ann-Kristin Mueller; Johannes Pfeil (Scientific Reports, 2018)
Abstract Cerebral malaria is a life-threatening complication of Plasmodia infection and a major cause of child mortality in Sub-Saharan Africa. We report that protection from experimental cerebral malaria in the rodent model is obtained by a single intravenous or subcutaneous whole-parasite immunization. Whole-parasite immunization with radiation-attenuated sporozoites was equally protective as immunization with non-attenuated sporozoites under chemoprophylaxis. Both immunization regimens delayed the development of blood-stage parasites, but differences in cellular and humoral immune mechanisms were observed. Single-dose whole-parasite vaccination might serve as a relatively simple and feasible immunization approach to prevent life-threatening cerebral malaria.